Sistem Informasi Akuntansi Dalam Kaitannya Dengan Laporan Biaya Produksi Pada Perusahaan CV Surya Pratama Gemilang - Iriyadi, Iriyadi; Pamungkas, Bambang; Gunawan, Lussar Gerrycia (Institut Bisnis dan Informatika Kesatuan, 2015)
Development of competitive businesses have triggered changes in the various methods of business management to streamline labor costs, overhead costs and raw material costs in improving product quality. Manufacturing companies are in a period of dynamic transformation that requires the manufacturers to always expand its business to survive and have strong competitiveness in addition to the company must have a strategy for its business organization, strategies must be developed by the company in addition to developing the company's products also must develop the data processing. Hopefully, by the system of all the activities of the company can be run according to plan and to minimize deviations or errors that occur which could harm the company. Object of research chosen by the authors is the company CV Surya Pratama Gemilang, a medium-sized manufacturing company that produces a variety of bacterial decomposition and laboratory equipment. The company has a systematic record system and computerized production and there are some systems that are still made manually as demandfor raw materials from the production to the warehouse with a wane sometimes only just though the procedure had to use a memo for taking raw materials from the warehouse. In doing production company CV Surya Pratama Gemilang processing raw materials into finished products based on processes that make the production process according to the requirement or determination of the bam, so when the warehouse inventory is less than the policysetting in the warehouse, the company started production to meet the needs of the provisions in the warehouse. From the nature of the production process suitable production cost calculation is based on the cost method (Process Costing). Keywords: Accounting Information Systems, report production costs, Cost Based Process